Exploring gender disparities in academic orthopaedic surgery faculty: analyzing subspecialty and leadership diversity to foster inclusivity - Malini Anand; Kaitlyn R. Julian; Mary K. Mulcahey; Stephanie E. Wong (Journal of Orthopaedic Surgery and Research)
Abstract Background The historic gap in gender diversity within orthopaedic surgery is widely acknowledged and continues to persist. The lack of female representation in orthopaedic surgery has been attributed to a variety of factors, including the absence of female mentors and leaders within the field. As such, we sought to examine the gender diversity among orthopaedic surgery faculty in various subspecialties at academic institutions and the distribution of female faculty in positions of leadership. Methods The American Medical Association Fellowship and Residency Electronic Interactive Database (FREIDA) was used to identify all allopathic orthopaedic surgery residency programs during the 2022 to 2023 academic year. The total number of faculty, and distribution of female faculty by subspecialty were collected from January to March 2023. The mean and percentage of female faculty in each subspecialty per program was calculated. Results The total number of orthopaedic surgery female faculty identified was 524. The subspecialty with the highest percentage of female faculty per program was pediatrics at 26.1% (148/511). Hand (18.6%; 113/511), oncology (19.2%; 38/511), foot and ankle (13.6%; 49/511), spine (3.9%; 21/511), shoulder and elbow (7.4%; 7/511) and adult reconstruction (3.7%; 24/511) had lower percentages of female faculty per program. A total of 52 (10.2%) female section chiefs were identified across all programs. Oncology had the highest percentage of female faculty represented in section leadership at 18.4% (7) and sports medicine had the lowest at 4.8% (4). Conclusion Gender diversity of faculty in orthopaedic surgery is low with adult reconstruction (3.7%), spine (3.9%), and shoulder and elbow (7.4%) having the lowest percentages of female faculty. The percentage of female faculty represented in section leadership is also lacking with a total of 52 (10.2%) female section chiefs identified across all programs. Increasing the number of females in leadership positions across all orthopaedic subspecialties may be one step in helping improve gender diversity in the field.